Cobalt‐Catalyzed Formation of Functionalized Diarylmethanes from Benzylmesylates and Aryl Halides. Issue 16 (20th June 2018) - Reddy, Bhoomireddy Rajendra Prasad; Chowdhury, Sushobhan; Auffrant, Audrey; Gosmini, Corinne
Abstract: A simple cobalt‐catalyzed reductive coupling protocol allowing the synthesis of functionalized diarylmethanes from benzyl mesylate is described. The possibility to directly use the benzyl alcohol as a result of a two‐step reaction is also presented. This method tolerates a variety of functional groups. A benzyl radical is likely involved. Abstract :